2021
DOI: 10.3390/ijms22094432
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Cryogenic Storage on Human Dental Pulp Stem Cells

Abstract: Dental pulp stem cells (DPSCs) are a type of easily accessible adult mesenchymal stem cell. Due to their ease of access, DPSCs show great promise in regenerative medicine. However, the tooth extractions from which DPSCs can be obtained are usually performed at a period of life when donors would have no therapeutic need of them. For this reason, it is imperative that successful stem cell storage techniques are employed so that these cells remain viable for future use. Any such techniques must result in high pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 69 publications
(53 reference statements)
1
22
0
Order By: Relevance
“…In addition, DPSCs express a variety of antigens associated with cell adhesion, growth factors, transcription regulation and multiple lineage-specific markers related to perivascular tissue, endothelium, immunogenic, neuronal and osteo/odontogenic tissues (Table 1). It is also noteworthy to mention that DPSCs express Major Histocompatibility Complex (MHC) class I antigens, but they do not express the immune co-stimulating molecules such as MHC class II antigen HLA-DR, CD40, CD80, and CD86 (Wada et al, 2009;Bhandi et al, 2021;Pilbauerova et al, 2021a). Kerkis et al, 2006;Atari et al, 2011;Liu L. et al, 2011;Ishkitiev et al, 2012;Kawanabe et al, 2012;Ponnaiyan et al, 2012;Huang et al, 2014;Wu et al, 2015;Ballini et al, 2019 Nanog Homeobox protein NANOG +++ Kerkis et al, 2006;Atari et al, 2011;Liu L. et al, 2011;Ishkitiev et al, 2012;Kawanabe et al, 2012;Ponnaiyan et al, 2012;Huang et al, 2014;Ballini et…”
Section: Dental Pulp Stem Cells Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, DPSCs express a variety of antigens associated with cell adhesion, growth factors, transcription regulation and multiple lineage-specific markers related to perivascular tissue, endothelium, immunogenic, neuronal and osteo/odontogenic tissues (Table 1). It is also noteworthy to mention that DPSCs express Major Histocompatibility Complex (MHC) class I antigens, but they do not express the immune co-stimulating molecules such as MHC class II antigen HLA-DR, CD40, CD80, and CD86 (Wada et al, 2009;Bhandi et al, 2021;Pilbauerova et al, 2021a). Kerkis et al, 2006;Atari et al, 2011;Liu L. et al, 2011;Ishkitiev et al, 2012;Kawanabe et al, 2012;Ponnaiyan et al, 2012;Huang et al, 2014;Wu et al, 2015;Ballini et al, 2019 Nanog Homeobox protein NANOG +++ Kerkis et al, 2006;Atari et al, 2011;Liu L. et al, 2011;Ishkitiev et al, 2012;Kawanabe et al, 2012;Ponnaiyan et al, 2012;Huang et al, 2014;Ballini et…”
Section: Dental Pulp Stem Cells Markersmentioning
confidence: 99%
“…In addition, DPSCs express a variety of antigens associated with cell adhesion, growth factors, transcription regulation and multiple lineage-specific markers related to perivascular tissue, endothelium, immunogenic, neuronal and osteo/odontogenic tissues ( Table 1 ). It is also noteworthy to mention that DPSCs express Major Histocompatibility Complex (MHC) class I antigens, but they do not express the immune co-stimulating molecules such as MHC class II antigen HLA-DR, CD40, CD80, and CD86 ( Wada et al, 2009 ; Bhandi et al, 2021 ; Pilbauerova et al, 2021a ).…”
Section: Dental Pulp Stem Cells Markersmentioning
confidence: 99%
“…The rationale behind these methods is the elimination or reduction of cellular damage caused due to ice crystal formation or dehydration that can be encountered while freezing cells. The optimal rate of slow freezing at which the viability and growth potential of the cells can be maintained and with minimal or no damage is 1°C to 2°C per min, and that of ultra-slow freezing is 0.3°C to 0.6°C per min (Pilbauerova et al, 2021). Some studies reported that these methods show better results in post-thaw cell viability and growth rate than the vitrification technique (Huynh et al, 2017).…”
Section: Controlled-rate Cryopreservationmentioning
confidence: 99%
“…Several studies have shown that DPSCs can be cryopreserved while retaining their stem cell properties ( Zhang et al, 2006 ; Gioventu et al, 2012 ). A recent study showed that DPSCs did not impair viability, proliferation, stemness, or differentiation capacity after cryopreservation at −80°C for 1 year ( Pilbauerova et al, 2021 ). Despite these advantages, DPSCs can be cryopreserved only when an appropriate number is obtained by isolating and culturing DPSCs from pulp tissue after tooth extraction.…”
Section: Dental Pulp Stem Cells As a Source Of Pulp Regenerationmentioning
confidence: 99%